Scalable synthesis of 3D porous germanium encapsulated in nitrogen-doped carbon matrix as an ultra-long-cycle life anode for lithium-ion batteries. Issue 38 (7th September 2021) - Liu, Xianyu; Wang, Yanting; Liu, Zheng; Wei, Huijuan; Ma, Mingguang; Xue, Rui; Zhang, Qianliang; Li, Shengying
Abstract : The 3D porous Ge/N-doped carbon nanocomposite preparation by encapsulating 3D porous Ge in a nitrogen-doped carbon matrix is reported, exhibiting excellent electrochemical performance for Li-ion batteries. Abstract : Germanium-based materials attract more interest as anodes for lithium-ion batteries, stemming from their physical and chemical advantages. However, these materials inevitably undergo capacity attenuation caused by significant volumetric variation in repeated electrochemical processes. Herein, we designed 3D porous Ge/N-doped carbon nanocomposites by the encapsulation of 3D porous Ge in a nitrogen-doped carbon matrix (denoted as 3D porous Ge/NC). The 3D porous structure can accommodate the volume change during alloying/dealloying processes and improve the penetration of the electrolyte. Furthermore, the doping of N in the carbon framework could introduce more defects and active sites, which can also contribute to electron transportation and lithium-ion diffusion. The half-cell test found that at a current density of 1 C (1 C = 1600 mA h g −1 ), the specific capacity stabilized at 917.9 mA h g −1 after 800 cycles; and the specific capacity remained at 542.4 mA h g −1 at 10 C. When assembled into a 3D porous Ge/NC//LiFePO4 full cell, the specific capacity was stabilized at 101.3 mA h g −1 for 100 cycles at a current density of 1 C (1 C = 170 mA h g −1 ), and the cycle specific capacity was maintained at 72.6 mA h g −1 at a high current density of 5 C. This work develops a low-cost, scalable and simple strategy to improve the electrochemical performance of these alloying type anode materials with huge volume change in the energy storage area.